ANALISIS FAKTOR YANG MEMENGARUHI MASYARAKAT SURABAYA BERWAKAF UANG DI LEMBAGA PENGELOLA WAKAF - Raja Surya Kusuma Riyadi (Islamic Economics and finance in Focus, 2023)
As time goes by, waqf continues to experience development with the presence of cash waqf in Indonesia. The potential of cash waqf is enormous, but its realization is still far away. This is caused by several factors that have not been optimal, including literacy, good governance, promotion, religiosity, and convenience. The research method used is a quantitative descriptive method by distributing questionnaires to the people of Surabaya who have interacted with waqf management institutions, including Lembaga Manajemen Infaq, Yayasan Dana Sosial Al Falah, Dompet Dhuafa, LAZIS Nurul Falah, and LAZNAS Nurul Hayat using a convenience sampling technique with sample calculation using Bernoulli as many as 96 respondents. The analysis was carried out with multiple linear regression and it was found that the variables of literacy, good governance, and convenience had a significant effect, while the promotion and religiosity variables showed no significant effect on the decision of the people of Surabaya to endow cash waqf in waqf management institutions